VEIN GRAFT PATENCY IN POST-CABG SYMPTOMATIC PATIENTS: AN ANGIOGRAPHIC STUDY - Shakeel Ahmad; Naeem Asghar; Athar Rauf (Journal of University Medical & Dental College, 2015)
ABSTRACTOBJECTIVE: To study the time taken for venous grafts to occlude or stenose after CABG in symptomatic patients.STUDY DESIGN: Cross-sectional study.PLACE AND DURATION OF STUDY: This study was carried out in the Cardiology ward and Department of Cardiac Catheterization & Interventional Cardiology of Punjab Institute of st thCardiology , Lahore, from 1 November, 2007 to 30 April, 2008.METHODOLOGY: One hundred post-CABG patients admitted in cardiology ward with symptoms of myocardial ischemia proceeding for coronary angiography were enrolled in the study. After taking history and clinical examination, the coronary angiography was done.RESULTS: Out of these 100 patients, 86 (86%) were males and 14 (14%) were females between 38-80 years of age. 53.3% of the grafts were patent in 6 months to 5 years duration after CABG. 21.4% grafts were patent in >10 years duration after CABG.CONCLUSION: Patients presenting within 5 years with symptoms of myocardial ischemia after CABG have more patent vein grafts. Patients with duration of >10 years after CABG have more diseased vein grafts.